MORE ON NEGATION IN BRAZILIAN PORTUGUESE - Cyrino, Sonia Maria Lazzarini (Estudos Linguísticos e Literários, 2024)
There is an innovative use for the negation in Brazilian Portuguese (henceforth, BP): the negative marker não ‘no’ (henceforth, ‘low não’) is possible in a position between the auxiliary and the uninflected verb in perfect and progressive periphrases. Since negation cannot appear in that position in other Romance languages, I discuss a possible analysis for this new construction. First, I discuss the properties of the possible ‘inhibited eventualities’ in Spanish (Fábregas; González-Rodríguez 2019, 2020, 2021) to check their similarities and differences with BP ‘low não’. Second, I consider which position could qualify as a syntactic position for ‘low não’ given its properties and the literature on multiple positions for negation (Declercq, 2013). Then, assuming Ramchand (2018)’s proposal, I propose that, differently from English, the auxiliary verbs of both these periphrases are generated inside vP in BP. Additionally, I assume that ‘low não’ became possible in BP due to the loss of lexical verb movement to a high functional category in the language. Thus, the lexical verb moves only as high as a lower (aspectual) projection, whereas the auxiliary separately moves up to a higher position (Cyrino, 2013; Cyrino; Araújo-Adriano, 2023).